Efficiency grounds and welfare effects in decoupling farm support. Insights from an AGE model of the Italian economy. (7th December 2006) - Cavalletti, Barbara; Rocchi, Benedetto
This paper investigates both efficiency and redistributive effects of the recent reform of Common Agricultural Policy in Italy. A general equilibrium model has been calibrated on a social accounting matrix of the Italian economy, adapted to represent the distribution of agricultural income between households. In simulation results the decoupling of farm support proves to be a welfare-improving policy. Moreover, this welfare effect is enhanced by redistributing the support towards low-income agricultural households. In terms of possible policy implications, simulation results suggest that redistributive effects in decoupling farm support may be a crucial aspect for the allocation of the EU agricultural budget.